2021
DOI: 10.1609/aaai.v35i6.16638
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Human Domain Knowledge to Warm Start Reinforcement Learning

Abstract: Deep reinforcement learning has been successful in a variety of tasks, such as game playing and robotic manipulation. However, attempting to learn tabula rasa disregards the logical structure of many domains as well as the wealth of readily available knowledge from domain experts that could help "warm start" the learning process. We present a novel reinforcement learning technique that allows for intelligent initialization of a neural network weights and architecture. Our approach permits the encoding domain k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…However, it has been found that approaches that rely on visual assessment can sometimes be misleading, as they may be specific to unique data or modelling conditions, and can be highly susceptible to outlying outputs that contradict the explanation [33][34][35]. Prior work has also sought to transform uninterpretable deep networks into interpretable architectures or modalities such as decision trees [12,13,36], or bayesian rule lists [14], and generate explanations by exploiting the "white-box" nature of these architectures [37].…”
Section: Explainable Ai Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been found that approaches that rely on visual assessment can sometimes be misleading, as they may be specific to unique data or modelling conditions, and can be highly susceptible to outlying outputs that contradict the explanation [33][34][35]. Prior work has also sought to transform uninterpretable deep networks into interpretable architectures or modalities such as decision trees [12,13,36], or bayesian rule lists [14], and generate explanations by exploiting the "white-box" nature of these architectures [37].…”
Section: Explainable Ai Methodologiesmentioning
confidence: 99%
“…Explanation Format -We chose XAI modalities that can all be generated from a single methodology presented in prior work [13]. This method converts learned policies into discretized decision trees which elucidate the decision making process within an AI-agent's policy [37].…”
Section: Experiments Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Warm Start Reinforcement Learning (WSRL) Cheng et al (2018); Zhu & Liao (2017) aims at initializing the policy of the agent with another policy pre-trained on the same task. Domain knowledge, i.e., information about the environment known by the designers but not initially known by the agent, can be used to kickstart learning, either through imitation learning on expert demonstrations Cheng et al (2018), directly encoding it via propositional rules in the neural network architecture of the agent Silva & Gombolay (2021), or actively learning to imitate a transferred policy Wexler et al (2022).…”
Section: Learningmentioning
confidence: 99%